PENGARUH HARGA DAN PENDAPATAN KONSUMEN TERHADAP PERMINTAAN JANUR DI DESA UBUD, KABUPATEN GIANYAR - SRI MAHARDANI, IA; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
for janur. The purpose of this research to analyze the influence prices of janur, ibung, and consumer income to a request janur and view its elasticity values. The sample in this study as 96 sample where determining sample using proportionate random sampling method. The analysis technique this research using multiple linear regression analysis double log model. The result is : 1) price of janur, price of ibung and consumer income has a positive and significant effect to number of requested in Ubud Village, Gianyar Regency. 2) Partially, price of janur, price of ibung and consumer income has a positive and significant effect to number of janur requested in village of ubud gianyar. 3) Judging from elastic value of inelastic jelly price of number of leaflets requested in Ubud Village. 4) Judging from value of price elasticity of ibung inelastic number of janur requested in Ubud Village. 5) Judging from cross elasticity of ibung is a substitute of janur, and, 6) Judging from elasticity of janur income is a giffen product because it defies the law of demand. Keywords: Price, Janur, Ibung, income, elasticity.